Carbon Sequestration in Terrestrial Pool A mitigation strategy to climate change - Ansari, M A; Baishya, L K; Singh, Deepak; Roy, S S; Prakash, N.; Ansari, M H; Lal, B (Indian Farming, 2018)
Benefits of carbon sequestration is enhancement of SOC pool, climate change mitigation, advancing food security and improving the environment depend on retention of crop residues as mulch. Carbon sequestration is integral tool to maintain bio chemical and biophysical variability of soil at optimum required level. For promotion of carbon sequestration at farmers’ field, government should start with public private partnership in the form of Carbon farming, treading C credits as another income stream, is an important strategy to provide incentives for promoting adoption conservation agriculture. For C trading to be effective, it is important to establish the fair/ transparent value of C based on the societal values and ecosystem services.